Impact of Merger on Financial Performance of Nepalese Commercial Bank - Acharya, Krishna Prasad (Journal of Balkumari College, 2020)
Mergers and Acquisitions have become the most widely used business strategy of restructuring and strong financial institution to achieve competitiveness, to ensure long term existence with suitable profitability, to forge entering in new markets, and to ascertain the capital base etc. Specially, the merger law policy-2068 and monetary policy 2072 issued by Nepal Rastra Bank, the regulatory body of banks in Nepal, have been experienced as the most effective weapons for merger and acquisition in Nepalese Banking industry. This study makes an attempt to the latest Monetary Policy lays down measures meant to encourage banks to merge. By Shrawan 2076, commercial banks are required to maintain an average interest rate spread (the difference between rates on loans and deposits) of 4.4 percent from the current 4.5 percent; banks that complete mergers and acquisitions by that time will get a one-year extension. Also, by Shrawan 2076, commercial banks are required to float at least 25 percent of their paid-up capital in debentures; banks that decide to tie the knot by that deadline will get a one-year reprieve. A merged bank also does not have to seek Nepal Rastra Bank's approval to open new branches. Currently, the board of directors, CEOs and deputy CEOs are required to abide by a cooling-off period of six months during which they cannot join another bank. This restriction will not apply to executives of a merged bank. The argument for mergers and acquisitions go something like this. There are just too many banks and financial institutions in Nepal. As of Ashad 2076, there were 28 commercial banks (Class A), 32 development banks (Class B), 24 finance companies (Class C) and 91 micro-credit companies (Class D). Conceivably, larger banks should be able to fund large infrastructure projects individually. The existence of larger Nepali banks could also make it easier for them to branch into India. Bigger Nepali banks will be able to compete with foreign banks better on Nepali soil.